Eksposisi Para-Aparavidya Upanisad dan Penetrasinya Dalam Pemahaman Masyarakat - Erviyanti, Duwik (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The ultimate goal of human life according to Hinduism is to achieve God’s consciousness or self-awareness. Consciousness is not only the body but also the atman (Jiva or Spirit). Through this awareness, one can fully realize that he has two types of needs in terms of knowledge, namely Para and Aparavidya. Paravidya is knowledge that learns about things that are far from the measure of human worldliness, namely God. Whereas Aparavidya knowledge is knowledge that learns about everything that is within the scope of creation. The Paravidya and Aparavidya are needed and do not negate or conflict with each other. This article descriptively reviews how these two types of knowledge live and develop in people’s daily lives. Spiritual development known as the Paravidya has its own peculiarities for the progress of human life in the past to the present. It is very interesting that human beings always aim to achieve something that is outside themselves as long as happiness is a concern. When they are unable to find happiness from outside, they turn around, which is to look inside and then find it there.